Forming of strengthening substructure in composition materials on the basis of aluminium - Lysyi, M. V.; Mozghovyi, O. V.; Biliuk, A. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
It has been proved in the paper, that the B-effect, that manifests itself in the temperature dependence of internal friction at 573 K, in the structurally fixed aluminium, is determined by reconservative movement of dislocations within the walls of bounds.